Utilization of local natural compounds: a practical step toward hygienic society, formulation of hand sanitizers and disinfectants - Yaqoob, Asim Ali; Mohd Azani, Nur Fatin Silmi; Ahmad Bhawani, Showkat; Mohamad Ibrahim, Mohamad Nasir; Abdul Latip, Ahmad Faiz; E.M. Yahaya, Nasehir Khan; Zarkasi, Kamarul Zaman; Mohamed Yusoff, Muhammad Azroie; Hamidon, Tuan Sherwyn; Hussin, M. Hazwan (Universiti Teknologi MARA (UiTM), 2024)
The most efficient technique to kill the germs is to use hand sanitizers and disinfectants. It is expected that there would be increasing demand for hand sanitizers, especially in light of the COVID-19 situation. In the present study, several essential oils were included in the formulation of alcohol-based hand sanitizers and disinfectants due to their antibacterial properties. The essential oil gives the hand sanitizer a pleasant scent, making it acceptable for use in public places. With the use of plant-based essential oils, antimicrobial hand sanitizers and disinfectants were effectively developed. The average amount of ethanol in hand sanitizers and disinfectants was determined to be 75.0 and 76.2 w/w %, respectively, with antimicrobial efficacy of 99.9%. The comparison of formulated and commercial hand sanitizers and disinfectants revealed that formulated hand sanitizers and disinfectants have outstanding antimycobacterial capabilities and are appropriate for commercialization